Anomeric 1,2,3-triazole-linked sialic acid derivatives show selective inhibition towards a bacterial neuraminidase over a trypanosome trans-sialidase - de Andrade, Peterson; Ahmadipour, Sanaz; Field, Robert A. (Beilstein Journal of Organic Chemistry, 2022)
Sialic acid is the natural substrate for sialidases and its chemical modification has been a useful approach to generate potent and selective inhibitors. Aiming at advancing the discovery of selective Trypanosoma cruzi trans-sialidase (TcTS) inhibitors, we have synthesised a small series of anomeric 1,2,3-triazole-linked sialic acid derivatives in good yields and high purity via copper-catalysed azide–alkyne cycloaddition (CuAAC, click chemistry) and evaluated their activity towards TcTS and neuraminidase. Surprisingly, the compounds showed practically no TcTS inhibition, whereas ca. 70% inhibition was observed for neuraminidase in relation to the analogues bearing hydrophobic substituents and ca. 5% for more polar substituents. These results suggest that polarity changes are less tolerated by neuraminidase due to the big difference in impact of hydrophobicity upon inhibition, thus indicating a simple approach to differentiate both enzymes. Moreover, such selectivity might be reasoned based on a possible steric hindrance caused by a bulky hydrophobic loop that sits over the TcTS active site and may prevent the hydrophobic inhibitors from binding. The present study is a step forward in exploiting subtle structural differences in sialidases that need to be addressed in order to achieve selective inhibition.
Keywords: inhibition; neuraminidase; sialic acid; trans-sialidase; 1,2,3-triazole

(untitled) - Burzyńska, P.; Sobala, Ł. F.; Mikołajczyk, K.; Jodłowska, M.; Jaśkiewicz, E. (Biomolecules, 2021)

(untitled) - Bowles, W. H. D.; Gloster, T. M. (Front. Mol. Biosci., 2021)

(untitled) - Glanz, V. Y.; Myasoedova, V. A.; Grechko, A. V.; Orekhov, A. N. (Drug Des., Dev. Ther., 2018)

(untitled) - Amaya, M. F.; Watts, A. G.; Damager, I.; Wehenkel, A.; Nguyen, T.; Buschiazzo, A.; Paris, G.; Frasch, A. C.; Withers, S. G.; Alzari, P. M. (Structure, 2004)

(untitled) - Lipničanová, S.; Chmelová, D.; Ondrejovič, M.; Frecer, V.; Miertuš, S. (Int. J. Biol. Macromol., 2020)

(untitled) - Yamashita, M. (Antiviral Chem. Chemother., 2010)

(untitled) - Shie, J.-J.; Fang, J.-M. (J. Biomed. Sci. (London, U. K.), 2019)

(untitled) - Mahal, A.; Duan, M.; Zinad, D. S.; Mohapatra, R. K.; Obaidullah, A. J.; Wei, X.; Pradhan, M. K.; Das, D.; Kandi, V.; Zinad, H. S.; Zhu, Q. (RSC Adv., 2021)

(untitled) - Cairo, C. W. (MedChemComm, 2014)

(untitled) - Guo, T.; Héon-Roberts, R.; Zou, C.; Zheng, R.; Pshezhetsky, A. V.; Cairo, C. W. (J. Med. Chem., 2018)

(untitled) - Guo, T.; Dätwyler, P.; Demina, E.; Richards, M. R.; Ge, P.; Zou, C.; Zheng, R.; Fougerat, A.; Pshezhetsky, A. V.; Ernst, B.; Cairo, C. W. (J. Med. Chem., 2018)

(untitled) - Campetella, O.; Buscaglia, C. A.; Mucci, J.; Leguizamón, M. S. (Biochim. Biophys. Acta, Mol. Basis Dis., 2020)

(untitled) - Freire-de-Lima, L.; Fonseca, L. M.; Oeltmann, T.; Mendonça-Previato, L.; Previato, J. O. (Glycobiology, 2015)

(untitled) - Arioka, S.; Sakagami, M.; Uematsu, R.; Yamaguchi, H.; Togame, H.; Takemoto, H.; Hinou, H.; Nishimura, S.-I. (Bioorg. Med. Chem., 2010)

(untitled) - Kim, J. H.; Ryu, H. W.; Shim, J. H.; Park, K. H.; Withers, S. G. (ChemBioChem, 2009)

(untitled) - Buchini, S.; Buschiazzo, A.; Withers, S. G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Figueredo, A. S.; de Andrade, P.; Riul, T. B.; Marchiori, M. F.; De Leo, T. C.; Fleuri, A. K. A.; Schenkman, S.; Baruffi, M. D.; Carvalho, I. (Pure Appl. Chem., 2019)

(untitled) - Meinke, S.; Schroven, A.; Thiem, J. (Org. Biomol. Chem., 2011)

(untitled) - Campo, V. L.; Sesti-Costa, R.; Carneiro, Z. A.; Silva, J. S.; Schenkman, S.; Carvalho, I. (Bioorg. Med. Chem., 2012)

(untitled) - Weïwer, M.; Chen, C.-C.; Kemp, M. M.; Linhardt, R. J. (Eur. J. Org. Chem., 2009)

(untitled) - Prescher, H.; Schweizer, A.; Kuhfeldt, E.; Nitschke, L.; Brossmer, R. (ChemBioChem, 2017)

(untitled) - Dedola, S.; Hughes, D. L.; Nepogodiev, S. A.; Rejzek, M.; Field, R. A. (Carbohydr. Res., 2010)

(untitled) - Carvalho, I.; Andrade, P.; Campo, V. L.; Guedes, P. M. M.; Sesti-Costa, R.; Silva, J. S.; Schenkman, S.; Dedola, S.; Hill, L.; Rejzek, M.; Nepogodiev, S. A.; Field, R. A. (Bioorg. Med. Chem., 2010)

(untitled) - Campo, V. L.; Carvalho, I.; Da Silva, C. H. T. P.; Schenkman, S.; Hill, L.; Nepogodiev, S. A.; Field, R. A. (Chem. Sci., 2010)

(untitled) - Tropper, F. D.; Andersson, F. O.; Braun, S.; Roy, R. (Synthesis, 1992)

(untitled) - Baker, A. N.; Richards, S.-J.; Guy, C. S.; Congdon, T. R.; Hasan, M.; Zwetsloot, A. J.; Gallo, A.; Lewandowski, J. R.; Stansfeld, P. J.; Straube, A.; Walker, M.; Chessa, S.; et al. (ACS Cent. Sci., 2020)

(untitled) - Han, X.; Shi, Y.; Si, L.; Fan, Z.; Wang, H.; Xu, R.; Jiao, P.; Meng, K.; Tian, Z.; Zhou, X.; Jin, H.; Wu, X.; et al. (MedChemComm, 2016)

(untitled) - Hori, H.; Nakajima, T.; Nishida, Y.; Ohrui, H.; Meguro, H. (Tetrahedron Lett., 1988)

(untitled) - Tiwari, V. K.; Mishra, B. B.; Mishra, K. B.; Mishra, N.; Singh, A. S.; Chen, X. (Chem. Rev., 2016)

(untitled) - He, X.-P.; Zeng, Y.-L.; Zang, Y.; Li, J.; Field, R. A.; Chen, G.-R. (Carbohydr. Res., 2016)

(untitled) - Meldal, M.; Diness, F. (Trends Chem., 2020)

(untitled) - Agrahari, A. K.; Bose, P.; Jaiswal, M. K.; Rajkhowa, S.; Singh, A. S.; Hotha, S.; Mishra, N.; Tiwari, V. K. (Chem. Rev., 2021)

(untitled) - Abdu-Allah, H. H. M.; Wu, S.-C.; Lin, C.-H.; Tseng, Y.-Y. (Eur. J. Med. Chem., 2020)

(untitled) - Neres, J.; Buschiazzo, A.; Alzari, P. M.; Walsh, L.; Douglas, K. T. (Anal. Biochem., 2006)

(untitled) - Neres, J.; Bonnet, P.; Edwards, P. N.; Kotian, P. L.; Buschiazzo, A.; Alzari, P. M.; Bryce, R. A.; Douglas, K. T. (Bioorg. Med. Chem., 2007)

(untitled) - Harrison, J. A.; Kartha, K. P. R.; Turnbull, W. B.; Scheuerl, S. L.; Naismith, J. H.; Schenkman, S.; Field, R. A. (Bioorg. Med. Chem. Lett., 2001)

(untitled) - Kim, C. U.; Lew, W.; Williams, M. A.; Liu, H.; Zhang, L.; Swaminathan, S.; Bischofberger, N.; Chen, M. S.; Mendel, D. B.; Tai, C. Y.; Laver, W. G.; Stevens, R. C. (J. Am. Chem. Soc., 1997)

(untitled) - Ferreo-Garcia, M.; Sanchez, D.; Parodi, A. (An. Asoc. Quim. Argent. (1921-2001), 1993)

(untitled) - Bellini, T.; Tomasi, M.; Dallocchio, F. (Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1993)

(untitled) - White, C. L.; Janakiraman, M. N.; Laver, G. W.; Philippon, C.; Vasella, A.; Air, G. M.; Luo, M. (J. Mol. Biol., 1995)

(untitled) - Buschiazzo, A.; Amaya, M. F.; Cremona, M. L.; Frasch, A. C.; Alzari, P. M. (Mol. Cell, 2002)

(untitled) - Šardzík, R.; Green, A. P.; Laurent, N.; Both, P.; Fontana, C.; Voglmeir, J.; Weissenborn, M. J.; Haddoub, R.; Grassi, P.; Haslam, S. M.; Widmalm, G.; Flitsch, S. L. (J. Am. Chem. Soc., 2012)